Big Data and Decision-Making: A Structured Literature Review - Berardino, Daniela Di; Vona, Simone (European Scientific Journal, ESJ, 2023)
This study provides a structured literature review on the role of Big Data (BD) and Big Data Analytics (BDA) in supporting the decision-making. The study aims to systematize the knowledge, the primary results and research gaps related to BD and BDA in strategic management and in decision-making, providing a future research agenda. Adopting the methodology of Massaro et al. (2015), the review investigates this phenomenon through a longitudinal approach, analyzing a sample of 97 articles published in high-level scientific journals ranked in ABS list, in the Marketing, Strategic Management, Ethics, Gender, and Social Responsibility area. The study unveils the subject of decisions, factors influencing good decisions and the main effects of using BD and BDA in decision-making. Public sector, non-profit organizations and SMEs deserve more attention. Similarly, new organizational factors, data chain dynamics and inhibitors must be explored to remove the obstacles in decision-making.